Unruptured Brain Arteriovenous Malformations: Primary ONYX Embolization in ARUBA (A Randomized Trial of Unruptured Brain Arteriovenous Malformations)-Eligible Patients. Issue 12 (December 2017) - Singfer, Uri; Hemelsoet, Dimitri; Vanlangenhove, Peter; Martens, Frederic; Verbeke, Luc; Van Roost, Dirk; Defreyne, Luc
Abstract : Background and Purpose—: In light of evidence from ARUBA (A Randomized Trial of Unruptured Brain Arteriovenous Malformations), neurovascular specialists had to reconsider deliberate treatment of unruptured brain arteriovenous malformations (uBAVMs). Our objective was to determine the outcomes of uBAVM treated with primary embolization using ethylene vinyl alcohol (ONYX). Methods—: Patients with uBAVM who met the inclusion criteria of ARUBA and were treated with primary Onyx embolization were assigned to this retrospective study. The primary outcome was the modified Rankin Scale score. Secondary outcomes were stroke or death because of uBAVM or intervention and uBAVM obliteration. Results—: Sixty-one patients (mean age, 38 years) were included. The median observation period was 60 months. Patients were treated by embolization alone (41.0%), embolization and radiosurgery (57.4%), or embolization and excision (1.6%). Occlusion was achieved in 44 of 57 patients with completed treatment (77.2%). Forty-seven patients (77.1%) had no clinical impairment at the end of observation (modified Rankin Scale score of <2). Twelve patients (19.7%) reached the outcome of stroke or death because of uBAVM or intervention. Treatment-related mortality was 6.6% (4 patients). Conclusions—: In uBAVM, Onyx embolization alone or combined with stereotactic radiosurgery achieves a high occlusion rate. Morbidity remains a challenge, even if it seems lower than in the ARUBA trial. Abstract : Supplemental Digital Content is available in the text.